2002
DOI: 10.1017/s0143385702001104
|View full text |Cite
|
Sign up to set email alerts
|

On the entropy theory of finitely-generated nilpotent group actions

Abstract: The entropy for actions of a finitely-generated nilpotent group G is investigated. The Pinsker algebra of such actions is described explicitly. The systems with completely positive entropy are shown to have a sort of 'asymptotic independence property', just as in the case of Z d-actions. The invariant partitions are used to prove that the property of completely positive entropy is equivalent to the property of the K-system (the property of the existence of special 'good' partitions). A complete spectral charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In this section, we briefly consider the entropy of actions of nilpotent countable torsion-free groups with a finite number of generators [17]. In this section, we briefly consider the entropy of actions of nilpotent countable torsion-free groups with a finite number of generators [17].…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we briefly consider the entropy of actions of nilpotent countable torsion-free groups with a finite number of generators [17]. In this section, we briefly consider the entropy of actions of nilpotent countable torsion-free groups with a finite number of generators [17].…”
Section: 1mentioning
confidence: 99%
“…Now, (F n ), n ∈ N is a Følner sequence of sets in G [17]. Now, (F n ), n ∈ N is a Følner sequence of sets in G [17].…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…We also prove that if α is a non-Bernoulli cpe action of , then α G is also non-Bernoulli and cpe. Indeed, it was shown by Cornfeld et al [3] that K -mixing is equivalent to cpe for Z-actions.Kamiński [17] extended Rokhlin and Sinai's approach to actions of Z d , d < ∞, and Golodets and Sinel'shchikov [12] proved the existence of perfect partitions for actions of the group of upper triangular matrices over Z and its subgroups. We construct such a family using refinements of the classical cutting and stacking methods.…”
mentioning
confidence: 99%
“…Kamiński [17] extended Rokhlin and Sinai's approach to actions of Z d , d < ∞, and Golodets and Sinel'shchikov [12] proved the existence of perfect partitions for actions of the group of upper triangular matrices over Z and its subgroups. However, it was demonstrated that the existence of such partitions for actions of the group Z ⊕ Z ⊕ Z ⊕ · · · is a more difficult problem which remains unresolved [18].…”
mentioning
confidence: 99%